Ultrasound-Guided Interventions in the Midfoot and Forefoot - Nwawka, O. Kenechi; Endo, Yoshimi (Seminars in Musculoskeletal Radiology, 2016)
Pathologic conditions in the midfoot and forefoot may be diagnosed and treated using image-guided intervention. Image-guided techniques to treat arthrosis, tendinopathy, nerve disorders, and other miscellaneous midfoot and forefoot conditions are described, with a focus on sonographic guidance.
Keywords: ultrasound-guided intervention; midfoot; forefoot